The Influence Of Double Branding Strategy On Consumer Appeal Of Bulog Public Corporation Regional Division Of Sulselbar In Makassar City - Winalda Adelia; Haedar Akib; Muh Rizal; Andi Aslinda (Universitas Negeri Makassar, 2020)
The aims of this research are (1) To know the overview of the double branding strategy of Bulog public corporation regional division of Sulselbar in Makassar city. (2) To know the influence factors of consumer attractiveness to KITA's products at Bulog of Sulselbar in Makassar city. (3) To know the influence of the double branding strategy model to consumer attractiveness at Bulog of Sulselbar in Makassar city. The type of this research is a simple regression analysis with a quantitative approach. To achieve the above aims using data collection techniques through observation, questionnaires, and documentation and analyzed using statistical formulas. The results showed that the double branding strategy had an effect on consumer attractiveness. with a correlation coefficient value of 0.775 and a coefficient of determination of 60.1 percent.